2017
DOI: 10.1038/s41598-017-03979-0
|View full text |Cite
|
Sign up to set email alerts
|

In Utero and Lactational Exposure Study in Rats to Identify Replacements for Di(2-ethylhexyl) Phthalate

Abstract: Di(2-ethylhexyl) phthalate (DEHP) and other phthalates are ubiquitous environmental contaminants with endocrine disrupting properties. Two novel plasticizers, 1,4 butanediol dibenzoate (BDB) and dioctyl succinate (DOS), have been proposed as potential replacements. Both have desirable properties as plasticizers and minimal in vitro biological effects. Herein, we present an in utero and lactational exposure study comparing DEHP with BDB, DOS, and 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH), a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 64 publications
(77 reference statements)
3
40
0
Order By: Relevance
“…Three of the four compounds were as effective, or indeed, more effective than commercially-available DEHP in all but one tested material property. In combination with previous studies that showed rapid environmental degradability [21,24,30] and a low toxicity profile [26,27,28,29,35], 1,5-pentanediol dibenzoate in particular stands out as a good candidate green plasticizer to replace DEHP, in addition to 1,3-propanediol dibenzoate and 1,6-hexanediol dibenzoate. Further, while 1,4-butanediol dibenzoate is not a good candidate for a drop-in replacement of DEHP, due to its observed material hardening, this study suggests its use as a reversible heat-activated plasticizer or processing aid, with excellent plasticizer properties at mildly elevated temperatures.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Three of the four compounds were as effective, or indeed, more effective than commercially-available DEHP in all but one tested material property. In combination with previous studies that showed rapid environmental degradability [21,24,30] and a low toxicity profile [26,27,28,29,35], 1,5-pentanediol dibenzoate in particular stands out as a good candidate green plasticizer to replace DEHP, in addition to 1,3-propanediol dibenzoate and 1,6-hexanediol dibenzoate. Further, while 1,4-butanediol dibenzoate is not a good candidate for a drop-in replacement of DEHP, due to its observed material hardening, this study suggests its use as a reversible heat-activated plasticizer or processing aid, with excellent plasticizer properties at mildly elevated temperatures.…”
Section: Discussionmentioning
confidence: 71%
“…Further, the proposed diol dibenzoate compounds could be good green candidates to replace phthalates, given previous work that identified their rapid biodegradation by soil bacteria [21,24,30]. Several toxicological in-vitro studies have also suggested a low hazard associated with these compounds [26,27,28,29,35], yet a more thorough toxicological analysis would likely be needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, there is a lack of information regarding the toxicity of and the fate of the metabolites of alternative plasticizers (which is particularly important given that many of the negative health effects associated with DEHP are known to stem from its metabolites rather than the parent compound), including toxicological endpoints such as carcinogenicity and endocrine disruption [40]. As new concerns have been raised about some of these DEHP replacements, such as DINP [11,41,42,43,44,45], it is increasingly important to produce truly green replacement plasticizers, with the factors advancing hazard reduction playing a bigger role in plasticizer development. Furthermore, with hundreds of commercial plasticizers available today for numerous applications, it is important to ensure that these and new plasticizers are evaluated and designed systematically and thoroughly, to avoid the “regrettable substitution” of one problematic compound with another [35].…”
Section: Historical Perspectivementioning
confidence: 99%